2013
DOI: 10.1016/j.jacc.2013.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Protease-Activated Receptor-2 Regulates the Innate Immune Response to Viral Infection in a Coxsackievirus B3–Induced Myocarditis

Abstract: Objectives This study sought to evaluate the role of protease-activated receptor-2 (PAR2) in coxsackievirus B3 (CVB3)–induced myocarditis. Background An infection with CVB3 leads to myocarditis. PAR2 modulates the innate immune response. Toll-like receptor-3 (TLR3) is crucial for the innate immune response by inducing the expression of the antiviral cytokine interferon-beta (IFNβ). Methods To induce myocarditis, wild-type (wt) and PAR2 knockout (ko) mice were infected with 105 plaque-forming units CVB3. Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 25 publications
5
89
2
Order By: Relevance
“…45 We found that murine embryonic CFs lacking PAR2 expressed higher levels of IFN-b and CCL5 expression after poly I:C stimulation compared with wild-type (WT) fibroblasts (Figure 4). 42 Taken together, these results indicate that PAR2 suppresses For personal use only. on April 29, 2019. by guest www.bloodjournal.org From TLR3-dependent expression of the antiviral pathway in both epithelial cells and CFs.…”
Section: Par2 Modulation Of Tlr2 Tlr3 and Tlr4 Signaling In Epithelmentioning
confidence: 75%
See 4 more Smart Citations
“…45 We found that murine embryonic CFs lacking PAR2 expressed higher levels of IFN-b and CCL5 expression after poly I:C stimulation compared with wild-type (WT) fibroblasts (Figure 4). 42 Taken together, these results indicate that PAR2 suppresses For personal use only. on April 29, 2019. by guest www.bloodjournal.org From TLR3-dependent expression of the antiviral pathway in both epithelial cells and CFs.…”
Section: Par2 Modulation Of Tlr2 Tlr3 and Tlr4 Signaling In Epithelmentioning
confidence: 75%
“…42 In vitro studies demonstrated that PAR2ko CFs either infected with CVB3 or stimulated with poly I:C expressed more IFN-b and CCL5 compared with WT cells. 42 Furthermore, activation of PAR2 inhibited poly I:C-induced phosphorylation of Stat1, which is activated downstream of IFN-b binding to its receptors. 42 These data suggest that is PAR2 suppresses the TLR3-TRIF-IFN-b pathway.…”
Section: Par2ko Mice Have Decreased Cvb3-induced Myocarditismentioning
confidence: 97%
See 3 more Smart Citations